SHOULD WE PROTECT THE CHILDREN AGAINST PNEUMOCOCCAL INFECTION? - A.A. Baranov; V.K. Tatochenko; L.S. Namazova (Вопросы современной педиатрии, 2008)
Diseases caused by streptococcus are a serious issue for the health care worldwide mostly due to wide spread, high lethal risk in the event of the severe run, increasing resistance of pneumococcus to antibacterial therapy, troubles with high efficiency of vaccines as pertaining to the special structure of the pathogen. Every year 1,6 mln people die of the diseases caused by pneumococcus worldwide, 50-70% of whom are children under 5 years. The highest morbidity falls onto the infants under 2 and younger and the elderly people. HIV infection and other immunodeficiency states increase the chance to get infected with pneumococcus caused diseases. There is a wide variety of pneumococci (about 90 serotypes) which have different degrees of virulence and pathogenesis. It is evident that on the one hand vaccines offered for the struggle against this dangerous infection should protect against the most widely spread and harmful serotypes and on the other hand should have a high degree of efficiency and safety for the one to be vaccinated. Today healthcare services make use of 7-valent conjugate polysaccharide-baleuronic vaccine (PCVB7) and nonconjugate polysaccharide vaccine against 23 serotypes. 23-valent vaccines are designed for the adolescent and elderly people, yet it is not licensed for the application among patients aged under2 who are the primary target group for the vaccination. PCVB7 incorporated serotypes causing invasive pneumococcal diseases among children in 60-85% of cases. The vaccine is well tolerated and deemed to be safe. It forms an express immune response (cellular, humoral, mucosal) and also reduces the nasopharyngeal bacteria carrying. This vaccine is highly immunogenic across all the age groups yet it is not licensed for the application among children under 5, including infants (under 12 months). Acknowledging high importance of diseases caused by pneumococci among infants, high efficiency and safety of PCVB7 in the given age group who suggests incorporating this vaccine into the national immunization calendars and immunization programmes, particularly in countries where mortality among children aged <5 years is >50/1000 live births or where >50 000 children die annually.Key words: pneumococcus, vaccine, children.